Design and fabrication of biochemical sensors: Innovative materials that enhance electrochemical transduction - Wan Salim, Wan Wardatul Amani (2017)
Projected increases in pollutants and waste products warrants the need for biochemical sensor–based monitoring technologies for efficient protection, remediation, and restoration of the environment, and also addresses the issue of homeland security. Efforts to develop biochemical sensors for environmental monitoring in projects funded by the Malaysia Ministry of Education (MOE) under the fundamental/basic grants and by private awards such as the L'Oréal-UNESCO award for applied research will be presented. Work has been done to optimize the electrochemical transducer layer of biochemical sensors in terms of stability, sensitivity, detection limit, and mechanical properties utilizing conductive polymers and/or graphene-based nanomaterial composites. Results show that electrochemical deposition of ethylene dioxythiophene (EDOT) and its conjugates as transducer layers can retain redox capability over multiple sensor use and provide stable current measurements in a water-flow test. Furthermore, Fourier transform infrared spectroscopy (FTIR) results reveal that methods of graphene oxide reduction affect sensor performance in terms of sensitivity and detection limit owing to the availability of surface functional groups. Biochemical sensors have been developed to successfully detect and quantify E. coli O157:H7 and ions involved in water-quality monitoring; the sensors are currently being integrated with portable platforms such as open-source microprocessors intended for field-work use.